Efektivitas Pelayanan Publik Pada Kegiatan PTSL di Kabupaten Pohuwato - Uno, Silva R.; Abdussamad, Zuchri; Abdussamad, Juriko (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study analyzes the effectiveness of public service in the Complete Systematic Land Registration (PTSL) program in Pohuwato Regency. The background highlights the need to evaluate service quality to ensure public satisfaction and smooth program implementation. The study employs a mixed-method approach with an explanatory sequential design, including SERVQUAL questionnaires, in-depth interviews, focus group discussions (FGD), and participatory observation. Findings reveal that the service effectiveness of PTSL is fairly good, yet all SERVQUAL dimensions show negative gaps between public expectations and perceptions. The largest gap is found in the tangible dimension (-0.94), while the smallest is in assurance (-0.56). Institutional factors are the most dominant in influencing service effectiveness (β=0.724), followed by human resources (β=0.689), technological infrastructure (β=0.567), and public participation (β=0.445). The main recommendations call for a holistic improvement approach emphasizing institutional strengthening, capacity building for human resources, upgrading physical facilities and technological infrastructure, and increasing public participation, including special programs for vulnerable groups. This study offers practical contributions by presenting a model to enhance public service effectiveness based on community participation and theoretical contributions by enriching the understanding of key factors influencing public service effectiveness in the context of the PTSL program.